Developing Multiplayer Online Game â€œKNIGHT FANTASY ONLINEâ€ - Darius Andana Haris; Viny Christiani Mawardi; Davin Pratama (Journal of Games, Game Art, and Gamification, 2020)
Knights Fantasy Online is a massively multiplayer online game with role-playing game genre. This game was developed using ActionScript 3.0 of Adobe Flash for client and Java for its server, while the design of the game was designed using Adobe Illustrator. This research is intended to make multiplayer online games using Adobe Flash. In this game, Players start their adventure in a world called Edenia as a knight from a kingdom called Aurum, the player is in charge of controlling the population of monsters. Players can take on quests, collect equipment and improve their character's ability. The game was tested by using Blackbox, alpha, beta and stress test. Through the results of a questionnaire distributed to 40 people. The test results shows that Knights Fantasy Online has an interesting gameplay, easy to understand and also has enough features as a massively multiplayer online game.